1985
DOI: 10.1002/ajh.2830200402
|View full text |Cite
|
Sign up to set email alerts
|

Chronic granulocytic leukemia: Correlation of elastic transformation type with karyotypic evolution

Abstract: Over a 3-year period, 26 patients with Philadelphia chromosome-positive chronic granulocytic leukemia were studied cytogenetically in both the chronic and blastic transformation phases of the disease; a further three patients were studied only after blastic transformation. Sixteen were considered to have adequate evidence of the type of transformation and form the basis of the report, where chromosome changes have been correlated with the morphological type of blastic transformation. Seven patients developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Conflicting results regarding their prognostic significance have been reported. Most authors have shown a definite correlation between additional abnormalities detected at the beginning of blast crisis and reduced survival [2,14,22,23,25,26], some did not find this association [1,6]. In our analysis, double Philadelphia chromosome and trisomy 8 were found to be associated with reduced survival in the univariate analysis; the latter retained prognostic significance in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 46%
“…Conflicting results regarding their prognostic significance have been reported. Most authors have shown a definite correlation between additional abnormalities detected at the beginning of blast crisis and reduced survival [2,14,22,23,25,26], some did not find this association [1,6]. In our analysis, double Philadelphia chromosome and trisomy 8 were found to be associated with reduced survival in the univariate analysis; the latter retained prognostic significance in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 46%
“…23 Most authors have shown that the finding of additional changes is associated with reduced survival, but this is not universally agreed. [24][25][26][27][28][29] In this study approximately 65% of patients had additional cytogenetic changes and evidence of cytogenetic evolution was an independent adverse prognostic factor for survival. Its presence, however, had no impact on response to first therapy.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that additional abnormalities as such are more common in myeloid than in lymphoid BC and that +8, +19, and, in particular, i(17q) characterize myeloid BC, whereas monosomy 7 and various, atypical additional changes are typically found in lymphoid BC [53, 69, 175, 176, 177, 178, 179, 180, 181, 182]. However, some studies have failed to corroborate these associations [51, 52], and reviewing available literature data (table 4), the only significant differences in cytogenetic evolution patterns between myeloid and lymphoid BC are a higher incidence of i(17q) in myeloid BC and higher frequencies of monosomy 7 and hypodiploidy in lymphoid BC.…”
Section: Secondary Aberrations In Relation To Morphologymentioning
confidence: 99%